Cost-effectiveness analysis of oral rehydration therapy compared to intravenous rehydration for acute gastroenteritis without severe dehydration treatment - Gabriela G. Mosegui; Cid M. Vianna; Marcus S. Rodrigues; Paula M. Valle; Frances V. Silva (Elsevier, 2019)
Background: Diarrhea causes, annually, approximately 1.7 billion cases and 760,000 deaths worldwide among children under 5 years of age, although these are preventable and treatable. This study aim to assess the cost-effectiveness for the treatment of diarrhea in emergency services in the management of children of acute gastroenteritis with non-severe dehydration. Methods: A stochastic decision tree model considering the perspective of the Brazilian public health system was used to calculate the cost-effectiveness of the 5 interventions: oral rehydration therapy (ORT) at home, and if it fails supervised ORT; they would receive; ORT at home, and if it fails intravenous rehydration therapy (IVT). ORT at home and if it fails, the half of them will receive supervised ORT, and the other half would receive IVT; Patient receives supervised oral treatment; Patient receives IVT. Quality-adjusted life year (QALY) was used to measure the clinical outcomes. Results: The strategy of initiating oral rehydration in children younger than 5 is the most efficient practice with a cost of $14.28 and effectiveness of 0.89 QALYs. Conclusion: ORT is an underutilized resource for the management of children with non-severe dehydration in emergency services. The overprescribed IVT increases cost without a corresponding significant increase in effectiveness. Keywords: Cost-benefit analysis, Gastroenteritis, Fluid therapy, Infusions, Intravenous